Catheter Ablation in Pediatric Wolff–Parkinson–White Syndrome – A Narrative Review - Gałach, Magdalena; Bernad, Mateusz; Widomska, Katarzyna; Bender, Aleksandra; Walczak, Paulina; Niewęgłowska, Małgorzata; Szymulewicz, Bartłomiej; Dąbrowski, Kacper; Łukaszewicz, Jakub; Krazińska, Oliwia (Quality in Sport, 2026)
Background. Wolff–Parkinson–White (WPW) syndrome is a frequent cause of supraventricular tachycardia in children and results from an accessory atrioventricular pathway causing ventricular pre-excitation. Although often asymptomatic, it carries a risk of serious arrhythmias and may impair cardiac function due to ventricular dyssynchrony. Catheter ablation is the main treatment for symptomatic patients and is increasingly considered in selected asymptomatic cases. Aim. This narrative review aims to summarize current evidence regarding the efficacy, safety, and functional outcomes of catheter ablation in pediatric patients with WPW syndrome. Methods. This narrative review analyzed selected clinical and observational studies involving pediatric patients with Wolff–Parkinson–White syndrome. Studies evaluating electrophysiological characteristics, ablation results, and functional effects were included and synthesized thematically, focusing on efficacy, safety, recurrence, and cardiac and exercise outcomes. Results. Available data suggest that catheter ablation achieves high acute success rates exceeding 85–90%, with overall long-term success approaching 99% after repeat procedures. Recurrence occurs in approximately 5–12% of cases but is usually effectively managed with re-ablation. The procedure demonstrates a favorable safety profile, especially when performed in specialized centers. Importantly, elimination of accessory pathway conduction may improve left ventricular function and reverse pre-excitation–related dyssynchrony. Preliminary evidence also suggests improvements in exercise capacity following successful ablation. Conclusions. Catheter ablation is an effective and safe treatment for pediatric WPW syndrome, offering not only arrhythmia control but also potential benefits in cardiac function and physical performance. Further prospective studies are needed to better define long-term functional outcomes and optimize management strategies in asymptomatic patients.